Waves and legacies: The making of an investment frontier in Niassa, Mozambique - Angela Kronenburg García; Patrick Meyfroidt; Dilini Abeygunawardane; Almeida A. Sitoe (Ecology and Society, 2022)
The literature on land-use frontiers has overwhelmingly focused on active frontiers of expansion. We focus on an emerging frontier. We studied the decisions, narratives, and practices of the actors driving land-use change in Niassa, Mozambique. Based on ethnographic research carried out between early 2017 and late 2018 among investors engaged in commercial agriculture and plantation forestry, we show how successive waves of actors with different backgrounds, motives, and business practices arrived in Niassa and attempted to establish farms or plantations yet repeatedly failed and left, or remained but continued to struggle. We show how even though waves come and go, they do leave sediments behind, legacies that over time add up to overcome the various constraints that investors face and gradually form the conditions for a frontier to emerge. We argue that the build-up of these legacies, particularly after the end of the civil war in 1992, has given rise to a new wave, which is qualitatively different from the previous ones in the sense that the actors did not arrive from elsewhere but were already present in Niassa. This wave thus emerges from within the region, building on the legacies of previous waves, indicating that over time endogenous processes may replace externally driven waves. We contribute to frontier theory by arguing that waves and legacies shape emerging frontiers through their dynamic interaction.
Keywords: 330; ethnography of investors; frontier emergence; land-use change; land-use investment; Mozambique; Niassa